WAYS TO REDUCE THE LEVEL OF NEGATIVE IMPACT OF CRISIS PHENOMENA ON SMALL BUSINESS ACTIVITIES - VASIUTA, Viktoriia; HORBUNOVA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study is devoted to possible ways to reduce the level of negative impact of crisis phenomena on the activities of small businesses. It plays an important role in the development of the national economy due to its flexibility and ability to quickly adapt to changes in the market. However, modern business faces numerous challenges, in particular crises that negatively affect its activities. The purpose of this study is to find measures to prevent the negative impact of crisis phenomena on the development of small entrepreneurship in Ukraine. The importance of taking into account the specifics of the activities of small companies in crisis situations is considered. Studying the impact of crisis phenomena on small businesses is important for developing effective strategies for survival, increasing resilience and adapting to economic changes. The main obstacles to business resumption are economic instability, unpredictability of government policy and the lack of solvent customers. In these conditions, the state and international partners actively support small businesses through various programs and grants. Developing measures to mitigate the effects of crises, such as a pandemic or martial law, can help ensure the stability of enterprises, preserve jobs and strengthen the confidence of consumers, partners and investors. Implementation of innovative management strategies, diversification of activities and digitalization of business processes are necessary steps to increase the sustainability of enterprises. In addition, equipment leasing is becoming a popular solution for relocated enterprises, which allows reducing capital costs and ensuring business continuity. The transition to a digital economy and online working formats is key to business survival during crises. Creating websites and using online marketing helps enterprises maintain contact with customers, expand their customer base and strengthen their presence in the virtual space. Thus, the study of the impact of crises on small businesses highlights the need for digital transformation and adaptation to the changing economic environment to ensure long-term success.